(untitled) (Fiep Bulletin - online, 2014)
The present work evaluates the relation between psychosocial stress, anxiety and the depression in the income of athlete of high performance. The study it was elaborated with a group of 20 female, with average age of 17 years, practitioners of the modality handball of high performance level. We use as instruments: Inventory of Stress de Lipp (ISSL) that presents 4 scales - alert, resistance, almost-exhaustion and exhaustion; Inventory Beck of anxiety (BAI) and Depression (BDI) that it is subdivided in minimum, moderate and serious. Results: The raised data had shown that 80% of the players present psychosocial stress. 20% of them presented stress in the alert phase, 60% of resistance and 10% of exhaustion. Regarding to the anxiety evaluation (BAI): 31% are presented in minimum phase of anxiety, 37% are concentrated in light phase and 26% in moderate phase. The same sample had as resulted in the depression test (BDI): minimum phase of anxiety 31%, light 58%, moderate 11%. Based on the results we can perceive that the most of the athletes are in the resistance phase. Being the activity developed in an environment that favors the appearance of stress, the athletes would have to present a bigger adaptation to the stressor events. It is verified that the higher levels of anxiety and depression are associated in the cases of stress. The data showed that, for this group of athletes, the elements that identify the necessity of accompaniment of stress are in the phases of resistance, almost-exhaustion and exhaustion and in the anxiety evaluation and depression in the phases moderate and serious.